2021
DOI: 10.21831/jppfa.v8i2.38300
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying pelajar SMA di media sosial: Prevalnsi dan rekomendasi

Abstract: Di era digital saat ini, bullying ditengarai hadir di ruang online atau yang sering disebut cyberbullying. Penelitian ini mengkaji realitas cyberbullying di media sosial yang dialami pelajar SMA Indonesia. Penelitian menggunakan pendekatan kuantitatif deskriptif. Lokasi penelitian di enam wilayah di Indonesia meliputi Aceh, Medan, Jakarta, Yogyakarta, Makassar, dan Papua. Setiap wilayah diwakili 3 sekolah dengan jumlah responden 242 setiap wilayah. Responden dalam penelitian ini adalah siswa SMA semua tingkata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…According to the findings of other research conducted at vocational high schools, bullying is an activity that inhibits the learning process in schools (Dardiri et al, 2015). The research results also confirm this discovery by Dwiningrum et al (Efianingrum et al, 2020), which indicates that bullying situations that often occur in high school can take many forms, such as mockery, defamation, physical assault, and cyberbullying. According to separate research, 21% of adolescents aged 12 to 18 reported being bullied at school (Facts About Bullying | StopBullying.Gov, n.d.).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to the findings of other research conducted at vocational high schools, bullying is an activity that inhibits the learning process in schools (Dardiri et al, 2015). The research results also confirm this discovery by Dwiningrum et al (Efianingrum et al, 2020), which indicates that bullying situations that often occur in high school can take many forms, such as mockery, defamation, physical assault, and cyberbullying. According to separate research, 21% of adolescents aged 12 to 18 reported being bullied at school (Facts About Bullying | StopBullying.Gov, n.d.).…”
Section: Introductionsupporting
confidence: 87%
“…Schools, which are ostensibly instructional environments that cultivate the value of importance and social control, are sites of violence. Bullying in schools is one of the difficulties that have not been adequately predicted (Efianingrum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor media sosial, kasus tentang bullying sering viral dimedia sosial, perilaku ini diulang-ulang dan murni dilakukan agar dapat membuat seseorang merasa terancam. Hal ini juga didukung pada penelitian (Efianingrum et al, 2020) bahwa semakin marak penggunaan gadget dan media sosial dapat membuat orang menjadi pelaku bullying.…”
Section: Metodeunclassified
“…Symbolic violence can occur in various situations, including in culture, neighborhood, family, and school, and also related to gender differences (Efianingrum, 2016). Meanwhile, in the context of campus culture, symbolic violence is a pattern of cultural and social domination that occurs unconsciously in campus life.…”
Section: Introductionmentioning
confidence: 99%